1992
DOI: 10.1002/mc.2940060406
|View full text |Cite
|
Sign up to set email alerts
|

Partial suppression of tumorigenicity in a human lung cancer cell line transfected with Krev‐1

Abstract: A human non-small-cell lung carcinoma cell line, Calu-6 (from an anaplastic carcinoma), was transfected with the Ki-ras-related anti-oncogene Krev-1. Several transfectant lines were obtained that showed a reduced tumorigenicity in nude mice with respect to the parental and control transfected cell lines. This decrease was approximately 50% in tumor incidence at 4 wk after subcutaneous inoculation of the transfected cells. In addition, the volume of the Calu-6 revertant-derived tumors was three to 10 times smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…This is the first evidence to suggest a role for the Krev-I gene in suppressing human prostate tumorigenicity. Partial suppression of tumor growth by the Krev-I gene has also been reported in human lung cancer cell lines [32]. In contrast, expression of transfected Krev-I in DU-145 cells did not result in a decrease in the doubling times or the in vivo tumorigencity, raising the possibility that the Krev-l suppressor gene does not have a growth inhibitory effect on prostate cancer cells which do not contain rus mutations.…”
Section: Discussionmentioning
confidence: 76%
“…This is the first evidence to suggest a role for the Krev-I gene in suppressing human prostate tumorigenicity. Partial suppression of tumor growth by the Krev-I gene has also been reported in human lung cancer cell lines [32]. In contrast, expression of transfected Krev-I in DU-145 cells did not result in a decrease in the doubling times or the in vivo tumorigencity, raising the possibility that the Krev-l suppressor gene does not have a growth inhibitory effect on prostate cancer cells which do not contain rus mutations.…”
Section: Discussionmentioning
confidence: 76%
“…While KRIT1 is a positive and indispensable regulator of Krev1 [33], the latter has been considered as a negative regulator of oncogenesis by competing with Ras for downstream targets [34]. KRIT1 is also able to interact with the integrin cytoplasmic domain associated protein-1-alpha (ICAP1a) [35,36], and it is mostly known because of its involvement in Cerebral Cavernous Malformations (CCMs), vascular lesions of the central nervous system (CNS) that can arise sporadically or may be inherited as autosomal dominant conditions with incomplete penetrance [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, expression of Rap1 completely suppressed the tumorigenicity of parental Hep3B cells. Caamano et al have shown that overexpression of rap1 gene partially suppresses the tumorigenicity of a lung cancer cell line Calu‐6 [32]. In polyomavirus middle T antigen‐transformed Rat‐2 cells, Rap1 also induces reversion of transformation [30].…”
Section: Discussionmentioning
confidence: 99%
“…Jelinek and Hassel have shown that rap1 gene induced the reversion of polyomavirus middle T antigen‐transformed Rat‐2 cells [30]. Most evidences supported the conclusion that overexpression of rap1 genes does induce reversion of malignant phenotypes in certain tumor cell lines [31,32]. However, an oncogenic effect of Rap1b has been reported in Swiss 3T3 cells, in which Rap1 increases DNA synthesis and cAMP exerts a stimulatory effect on cell growth [33].…”
Section: Introductionmentioning
confidence: 94%